(untitled) (Global Journal of Human-Social Science, 2024)
This paper analyzed Brazilian authors works on school administration focusing on the 1930-1969 period to construct a historical perspective on principals training One of the main difficulties of the research was defining its study object Although we could highlight the main aspects of principals training in Brazil within the selected time frame there was difficulty in constructing the inferences The methodology adopted is qualitative and exploratory in nature For the analysis we employed Content Analysis categorizing the material which represents each of the decades according to the rule of homogeneity One of the main findings reveals that the field of study concerning principals training has advanced very little This stagnation is attributed to the fact that Brazil had virtually no investigations on the topic for four decades Nonetheless the period analyzed exhibited several significant initiatives aimed at principals initial and continuing training which could be considered pioneering efforts in Brazil